Insights from Key Stakeholders on the Development of Graphic Design Education in China - JEFF POON CHAK KIN (International Journal of Multidisciplinary Research and Studies, 2023)
This research looks at how the Chinese art curriculum helps students become ready for their first jobs. The study uses questionnaires to collect information from participants (students, instructors, and art experts). According to the results, students place higher importance on design abilities than they do on professional skills (such as written communication, oral presentations, and critical analysis) (theory, principles, techniques, craft, etc). ...everything having to do with computers, programming, or writing code. Therefore, art education should teach students more than only how to get their job done on time and in a professional manner, such as how to use programs like Photoshop and web design to create effective and efficient designs. And, maybe even more importantly, the ability to effectively communicate with customers, colleagues, and superiors.